2023
DOI: 10.1007/s40618-023-02128-x
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoiesis in Cushing syndrome: sex-related and subtype-specific differences. Results from a monocentric study

Abstract: Context Cushing syndrome (CS) is associated with different hematological abnormalities. Nevertheless, conflicting data about erythropoiesis in CS have been reported. Furthermore, it is unclear whether CS sex and subtype-specific alterations in red blood cells (RBC) parameters are present. Objective To investigate sex and subtype-specific changes in RBC in patients with CS at initial diagnosis and after remission. Design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
2
10
2
Order By: Relevance
“…Thus, similar non-invasive protocols should be evaluated and validated in other settings using these and other emerging modalities such as desmopressin stimulation test, and CRH-receptor targeted molecular imaging (68Ga-CRH-PET-CT) [31,32]. Recent studies have also shown subtype-specific differences in hematological parameters between CD and EAS [33,34]; further validation of these findings and incorporation in future non-invasive models would add value. To conclude, using simple and non-invasive alternative strategies, BIPSS could be avoided in 41 % and peripheral CRH stimulation in 22 % of patients with ACTH-dependent CS and no macroadenoma, in whom these procedures would have otherwise been recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, similar non-invasive protocols should be evaluated and validated in other settings using these and other emerging modalities such as desmopressin stimulation test, and CRH-receptor targeted molecular imaging (68Ga-CRH-PET-CT) [31,32]. Recent studies have also shown subtype-specific differences in hematological parameters between CD and EAS [33,34]; further validation of these findings and incorporation in future non-invasive models would add value. To conclude, using simple and non-invasive alternative strategies, BIPSS could be avoided in 41 % and peripheral CRH stimulation in 22 % of patients with ACTH-dependent CS and no macroadenoma, in whom these procedures would have otherwise been recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations of hematological parameters which are observed in patients with CS (e.g. neutrophilia, lymphopenia, anemia in males) typically improve after remission of hypercortisolism [45,46]. However, detailed information on the distinct changes of hematological parameters during medical therapy have not been reported yet.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, as mineralocorticoid precursors often increase under 11β-hydroxylase inhibitors, potassium levels may also worsen during treatment [3]. Alterations of hematological parameters observed in patients with CS (e. g., neutrophilia, lymphopenia, anemia in males) typically improve after remission of hypercortisolism [45,46]. However, detailed information on the distinct changes in hematological parameters during medical therapy has not been reported yet.…”
Section: Drug Monitoringmentioning
confidence: 99%
“…In addition to the classic constellation of signs and symptoms, CS has been shown to in uence patients' hematological pro les: anemia [9,10], polycythemia [11][12][13], leukocytosis [9,14,15], lymphopenia [16], and proliferation of in ammatory markers [17] have all been reported. Most trends were identi ed in particular demographic groups of a patient population.…”
Section: Introductionmentioning
confidence: 99%